Sacrificial relics or trophies? Animal heads in Bronze Age Crete - Shapland, A (Peeters Publishers, 2021)
Animal heads appear in a variety of different places in Bronze Age Crete. Animal skulls were deposited at a number of sites in the Middle and Late Bronze Age and are usually regarded as coming from sacrifices, particularly following Sir Arthur Evans's interpretation of such a deposit at the House of the Sacrificed Oxen. Animal head rhyta, made from clay or elaborately carved in stone, are often similarly regarded. Animal heads are also part of Bronze Age scripts from the beginning, and appear widely on seals. These tend to be seen as more symbolic. This paper will suggest that animal heads were significant things in themselves and were used in the commemoration of the consumption of particular animals. This shifts the focus from the act of killing, which does not leave a material trace, to the subsequent treatment of the animal body, which does. Whereas the body was eaten, the evidence suggests that the head was sometimes retained as a fleshy trophy. It was the particular uses of the animal head in Bronze Age Crete that connects these various phenomena of deposited skulls and animal heads in iconography.